Modafinil attenuates the neuroinflammatory response after experimental traumatic brain injury - (:unkn) unknown (My University, 2021)
BACKGROUND: Modafinil has been proven to exert anti-inflammatory, anti-oxidative and neuroprotective effects on numerous neurological disorders. However, its effects after traumatic brain injury (TBI) has not been yet explore. This study aimed to explore if Modafinil can attenuate the neuroinflammatory phase of TBI and clarify the possible underlying mechanisms. METHODS: A weight drop model was used to induce experimental TBI on 30 Wistar albino rats. The treatment group received Modafinil on the day of the trauma and the following 5 days. Garcia Test was used to assess for neurological status and histopathological examination along with biochemical analysis of NSE, S-100B, CASP3, and TBARS levels were performed. RESULTS: Rats treated with Modafinil after the trauma had a statistically significant higher Garcia test score (p<0.001) and presented with increased evidence of anti-inflammatory and neuroprotective effect (p<0.05, p=0.005). Decreased levels of all biochemical parameters with NSE, CASP3, and TBARS having statistical significance was observed (p<0.05). CONCLUSIONS: The findings of this paper support the notion that a psychoactive drug Modafinil, traditionally used for sleep disorders and also known as a cognitive enhancer may prove beneficial in decreasing mortality and morbidity after TBI through anti-inflammatory, anti-oxidative and neuroprotective effects.